The Effect of Incubation Time for Green Lamtoro Fertilizer on the Growth and Yield of Eggplant ‘Gelatik” in Alluvial Soils - Devi Rumaisyah; Eddy Santoso; Siti Hadijah (Jurnal Sains Pertanian Equator, 2020)
This study aimed to obtain the best incubation duration of green lamtoro fertilizer for the growth and yields of eggplant “gelatik” on alluvial soils. The study was conducted at Permata Hijau Complex, Jalan A. Yani 2, Pontianak, by June 29 to November 11 2018. This study used a Completely Randomized Design (CRD) consisting of 5 treatments, 4 samples and 4 replications. The treatments were set as p1 i.e lamtoro leaves without incubation, p2 1 week incubation of lamtoro leaves, p3 2 weeks incubation of lamtoro leaves, p4 3 weeks incubation of lamtoro leaves and p5 4 weeks incubation of lamtoro leaves. Observed variables were plant height, number of leaves, stem diameter, root volume, dry weight of plants, number of fruits per plant, and weight of fruits per plant. The results showed that the effect of incubation duration of green lamtoro leaves fertilizer had a significant effect on all observed variables. As a conclusion, the application of green lamtoro leaves fertilizer incubated for 3 weeks noted as the best growth and yield of eggplant “gelatik” on alluvial soil.Keywords: alluvial, lamtoro leaf, eggplant, green fertilizer.